Analysis of herpes zoster events among Bortezomib-treated patients in the phase III APEX study - Chanan-Khan, Asher A. A.; Sonneveld, Pieter; Schuster, Michael W.; Stadtmauer, Edward A.; Facon, Thierry; Harousseau, Jean-Luc; Ben-Yehuda, Dina; Lonial, Sagar; Goldschmidt, Hartmut; Reece, Donna; Neuwirth, Rachel; Anderson, Kenneth C.; et al. (Journal of clinical oncology, 2008)
Purpose - - The aim of this subset analysis was to determine if bortezomib treatment is associated with increased incidence of varicella-zoster virus (VZV) reactivation in patients with relapsed multiple myeloma (MM). - - Patients and Methods - - Incidence of herpes zoster was evaluated in 663 patients with relapsed MM from the phase III APEX trial comparing single-agent bortezomib with high-dose dexamethasone. - - Results - - Bortezomib was associated with a significantly higher incidence of herpes zoster compared with dexamethasone treatment (13%, 42 of 331 v 5%, 15 of 332; P = .0002). Most herpes zoster infections were grade 1/2; incidences of grade 3/4 events (1.8% v 1.5%) and infections considered serious adverse events (1.5% v 0.9%) were similar between treatment arms, and no herpes zoster-related deaths occurred. Neither the time to onset of the herpes event nor the patients’ absolute lymphocyte counts at baseline differed significantly between arms. VZV reactivation was the only herpes viral event noted to be significantly elevated in the bortezomib treatment group compared with the dexamethasone treatment group (P = .0002). The incidence of non-VZV-related herpes viral infections was comparable between arms. No additional risk factors for herpes zoster reactivation were identified. - - Conclusion - - Further studies are needed to explain these observations and their implications; however, for patients treated with bortezomib or bortezomib-containing regimens, the risk of VZV reactivation should be monitored and routine use of antiviral prophylaxis considered.
Published online ahead of print at www.jco.org on August 18, 2008
Gesehen am 14.01.2022